Investigation of Self-Esteem Levels of the Candidates Participated in Special Talent Exam - Ozmutlu, Ilker; Kara, Erhan (Asian Journal of Education and Training, 2020)
The purpose of study is to investigate the self-esteem levels of the candidates who participated in the special talent exam (STE) through various variables. The study group consists of 129 female and 649 male, 778 participants in total attending STE conducted by Tekirdağ Namik Kemal University School of Physical Education and Sport in 2018. In the research conducted with the relational screening model method, personal information form developed by the researcher and “Rosenberg Self-Esteem Scale” developed by Rosenberg (1965) whose Turkish adaptation studies were carried out by Cuhadaroğlu (1986) have been used in order to determinate self-esteem levels of the participants in STE. The scale consists of 10 items in 4 point Likert type. Cronbach Alpha coefficient for reliability is .81. At the end of the study; it was found that there was no significant relationship between the self-esteem levels of the candidates and gender variable, TYT (Basic Proficiency Test) score, geographical region of residence and the high school type of graduation. A positive and low level of relationship was found between the self-esteem levels of the candidates and the sports branch variable.